Alice's Adventures in Wonderland : Through the Looking-Glass and Other Writings - Carroll, Lewis; Introduction By Robin Denniston and Illustrations Copied from Tenniel by Dorthy Colles (New Dehli Rupa.Co, 2003)
A children's classic published in 1865, this book tells the story of alice and her dreams as she pursues a white rabbit to meet the duchess, cheshire cat, mad hatter and several other colorful characters. In the other two stories, alice meets tweedledum, tweedledee, humpty dumpty and the lion and the unicorn.
Include Illustrations.
Keywords: Alice (Fictitious character from Carroll) -- Imaginary Places -- Juvenile Fiction